إعداد الأجر في المؤسسات الإقتصادية - حمزة, لبيهي; مروة, لبيهات; عبد الحق, منصوري (جامعة الوادي - University of Eloued, 2023)
"حاولنا ضمن هذه الد ارسة التطرق لموضوع قد ناال إ هتمام اإلقتصاديين والهيئات اإلقتصادية للدولة باإلضافة إلى المؤسسات والدول أال وهو موضوع األجور وطريقة معالجته محاسبيا في المؤسسات العمومية والعوامل التي تؤثر فيه وتتأثر به. يرجع إ هتمام المجتمعات الحديثة بموضوع األجور ومحاسبته الخاصة به ففي المؤسسات العمومية إلى آثاره على مختلف المجاالت في الدولة, فهي تؤثر على االقتصادوالظروف االجتماعية داخل البلد . فمن الناحية االقتصادية تلعب االجور دورا فعاال في توفير الظروف المناسبة لعملية التنمية اإلقتصادية, وبالتالي زيادة اإلنتاج, و ارتفاع األرباح, أما بالنسبة للمؤسسة تعتبر األجور من أهم عناصر التكاليف ومن الناحية االجتماعية فهي تساهم في توزيع الدخل الوطني على أفراد المجتمع لضمان العيش الكريم للفرد وألسرته, ألنه يعتبر كوسيلة لتلبية حاجياته ورغباته وتحسين مستواه المعيشي. يعتبر األجر رابطة قوية بين المؤسسات والعامل في التأثير على سلوك كل منهما, ولألجور دور كبير في دفع العمال إلى تحقيق أهداف المؤسسة مهما كان قطاع النشاط , كما أن تنظيمه يؤدي إلى تفادي النزاعات و الخالفات وهذا يؤدي إلى الرغبة في العمل بالنسبة لألفراد وبالتالي يؤثر على مستوى إنتاجيتهم وعلى كفاءة المؤسسة, ولهذا فإن تحديد األجور هي من العناصر التي تؤثر على رفع اإلنتاجية وتخفيض التكاليف بالنسبة للمؤسسة." "In this study, we tried to address a topic that has attracted the attention of economists and economic organizations. For the state in addition to institutions and countries, namely, the issue of wages and the method of accounting for it Public institutions and the factors affecting and affected by it. The interest of modern societies in the issue of wages and its own accounting for it is due to the institutions Generality refers to its effects on various fields in the state, as it affects the economy and conditions social within the country. From an economic point of view, wages play an effective role in providing the appropriate conditions for the development process economic, and thus increase production, and High profits, as for the institution wages are considered from The most important elements of costs and from a social point of view, they contribute to the distribution of national income among individuals Society to ensure a decent life for the individual and his family, because it is considered as a means to meet his needs and desires and improve their standard of living. Wage is a strong bond between institutions and the worker in influencing the behavior of each, and for wages A major role in pushing workers to achieve the objectives of the establishment, whatever the sector of activity, and organizing it It leads to avoiding conflicts and disagreements, and this leads to the desire to work for individuals and thus It affects the level of their productivity and the efficiency of the organization, and for this reason, setting wages is one of the elements Which affect the increase in productivity and reduce costs for the organization."
Keywords: الأجر، المؤسسات الإقتصادية